Artikel Karawitan Composition Jujug Luang | Komposisi Karawitan Jujug Luang - I Putu Oka Rudiana; Ni Ketut Suryatini; I Gede Mawan (GHURNITA: Jurnal Seni Karawitan, 2022)
The purpose of the work of Jujug Luang is to be able to become a motivation in a process of creating a musical compositional work of art that can inspire in terms of art as well as being a medium for taste and aesthetic processing in a process of creating musical works of art. This work was motivated by the stylist's desire to transform the procession of melasti, tawur, nyepi and ngembak geni ceremonies into musicals by using the percussion compositions created by the gamelan semarandhana as a form of creating creative works of Balinese music through a process that requires skills and skills as well as motivation to bring about renewal of tradition. The stages of the process in this creative percussion are the exploration stage, the experimental stage (improvisation), the forming stage. This work uses a creative percussion structure including (1) Pengawit which describes the atmosphere of the melasti procession, (2) Gengenderan which describes melasti by actualizing the atmosphere of the waves, (3) Bapang describes the Tawur, and (4) pengcet describes the Ngembak Geni.